2015
DOI: 10.1007/s10865-015-9637-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of inflammatory markers in explaining the association between depression and cardiovascular hospitalisations

Abstract: This study investigated whether inflammation may explain the relationship between depression and incident cardiovascular hospitalisations. Participants (55-85 years) completed baseline depression and physical assessment. Those without self-reported cardiovascular events were followed prospectively for hospital admissions for angina, myocardial infarction and cerebral infarction (median 937 days). Across 5140 person-years of risk (N = 1692), there were 47 incident cardiovascular hospitalisations (2.8 %). Contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 70 publications
(83 reference statements)
0
20
0
1
Order By: Relevance
“…In addition, circulating levels of IL-6 have been associated with the efficacy of antidepressant therapy, with lower IL-6 being linked to more favourable treatment effects (Janssen et al 2010;Hannestad et al 2011;Hiles et al 2012;Cattaneo et al 2013), and high IL-6 levels to refraction to antidepressants (Lanquillon et al 2000;O'Brien et al 2007;Yoshimura et al 2009). We add to the existing evidence by reporting findings among a large nonclinical cohort of participants followed on average for 6 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, circulating levels of IL-6 have been associated with the efficacy of antidepressant therapy, with lower IL-6 being linked to more favourable treatment effects (Janssen et al 2010;Hannestad et al 2011;Hiles et al 2012;Cattaneo et al 2013), and high IL-6 levels to refraction to antidepressants (Lanquillon et al 2000;O'Brien et al 2007;Yoshimura et al 2009). We add to the existing evidence by reporting findings among a large nonclinical cohort of participants followed on average for 6 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether IL-6 is implicated in the prognosis of these disorders is unclear. Previous small-scale studies of depressed patients suggest that IL-6 levels might decrease amongst those who recover following antidepressant treatment (Janssen et al 2010;Hannestad et al 2011;Hiles et al 2012;Cattaneo et al 2013;Yang et al 2015). These studies did not examine whether the baseline IL-6 levels predicted recovery from depressive symptoms.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…And the inflammatory response mediated by them plays an important role on the damage process of neurological function after cerebral infarction [21]. TNF-α can directly cause the inflammatory injury on neuron and gliocyte, which has also the chemotaxis of inflammatory cell [22].…”
Section: Discussionmentioning
confidence: 99%
“…Trait Anxiety, appears to play a differing role to depression in the exacerbation of eczema; whilst higher depression has been associated with increased severity of eczema (Arima et al, 2005), state and trait anxiety has been found to be associated with increased duration of the illness (Kim et al, 2006) Neurotic people are more prone to stress and recently Kuebler and colleagues showed that stress induces increases in NF-jB-BA that relate to subsequent mRNA expression of proinflammatory (Kuebler, Zuccarella-Hackl, Arpagaus, Wolf, Farahmand, von Känel, &Wirtz, 2015). Further, there appear to have sex effects on the association between depression and inflammatory markers; stress may drive inflammation and subsequent depressive symptoms shown in women, not in men (Hiles, Baker, de Malmanche, McEvoy, Boyle, & Attia, 2015).…”
Section: Introductionmentioning
confidence: 99%